Country Statistical Capacity: A Recent Assessment Tool and Further Reflections on the Way Forward - Hai-Anh H. Dang; Dean Jolliffe; Umar Serajuddin; Brian Stacy (Global Labor Organization (GLO), 2024)
A country's statistical capacity takes an indispensable part in its development. We offer a comprehensive comparison between the World Bank's Statistical Performance Indicators and Index (SPI) and its predecessor, the Statistical Capacity Index (SCI) regarding different conceptual and empirical aspects. We further examine the relationships of the two indexes with some agriculture development indicators such as food security, food sustainability and productivity as well as other key indicators including headcount poverty, GDP per capita, and an SDG progress index. Our analysis employs the latest SPI data update in 2022, which were not available in previous studies. We also propose clear guidelines on how the SPI can be maintained and updated in the future to ensure that this process is transparent, replicable, safeguarded with high quality, and provides comparable data over time.
Keywords: C8; H00; I00; O1; 330; statistical capacity; statistical performance; statistical capacity index; national statistical system; food security